Investigation of Dynamic Load Characteristics for Rolling Bearing - Zheng, Si-Jia; Luo, Zhong; Yang, Yao-Jia; Xu, Di; Yan, Xiao-Lu (Journal of Vibration Testing and System Dynamics, 2026)
For cylindrical roller bearing, a dynamic model considering the degree of freedom of the rollers is established to analyze the influence of the external load and clearance on dynamic characteristics of rolling bearing. Firstly, the load distribution curve is compared with Hou’s test data to verify the validity of the bearing dynamic model. Then, load distribution curves and the fixed point load sequences are calculated under different clearances. And the angular position equations of bearing components at the moment of the load mutation occurs at the fixed points on inner and outer raceways are established for analyzing the law of the load sequence variation. Finally, the load sequences of the danger points of inner raceway and outer raceway are calculated under the coupling effect of radial load and unbalanced load. The results show that the load sequence varies periodically and the period is determined by the angular position deviation of the fixed point when the first and the last contact occurs during the point rotates in one turn. Without considering the unbalanced load, the load distribution curve can completely envelop the contact load sequence at the fixed point of the inner ring raceway, and with the increase of the clearance, the span of the envelope peak of the load sequence decreases and the height increases.